Odpowiedź :
2(x-1)+3(y-2)=5
2x - 2 + 3y - 6 = 5
2x = 13 - 3y / 2
x = 6,5 - 1,5y
3(x-y)-2(x-2)=7
3x -3y - 2x +4 = 7
x = 3 + 3y
2x - 2 + 3y - 6 = 5
2x = 13 - 3y / 2
x = 6,5 - 1,5y
3(x-y)-2(x-2)=7
3x -3y - 2x +4 = 7
x = 3 + 3y
2(x-1)+3(y-2)=5
3(x-y)-2(x-2)=7
2x - 2 +3y - 5 = 5
3x - 3y - 2x +4 = 7
3y się skreśla
i juz masz tylko z jadna niewiadomą zadanie
3(x-y)-2(x-2)=7
2x - 2 +3y - 5 = 5
3x - 3y - 2x +4 = 7
3y się skreśla
i juz masz tylko z jadna niewiadomą zadanie
2(x-1)+3(y-2)=5
3(x-y)-2(x-2)=7
2x-2+3y-6=5
3x-3y-2x+4=7
2x+3y=13
x-3y=3
3x=16 /:3
x=5⅓
5⅓-3y=3
-3y= -1⅔
-3y=-⁵/₃ /×(-3)
9y=5 /:9
y=⁵/₉
3(x-y)-2(x-2)=7
2x-2+3y-6=5
3x-3y-2x+4=7
2x+3y=13
x-3y=3
3x=16 /:3
x=5⅓
5⅓-3y=3
-3y= -1⅔
-3y=-⁵/₃ /×(-3)
9y=5 /:9
y=⁵/₉